Biogeochemical dynamics of dissolved organic matter in the Changjiang Estuary during a late flooding season - Zhongqiao Li; Ruoshi Zhao; Xiao Ma; Xiaona Wang; Liang Su; Hongliang Li; Haiyan Jin; Jiangning Zeng; Jianfang Chen (Frontiers in Marine Science, 2025)
To address the knowledge gap concerning the behavioral dynamics of dissolved organic matter (DOM) in the Changjiang Estuary during the late flooding season, we conducted an extensive sampling campaign during which 188 water samples were systematically collected across the estuary from August 15th to September 4th, 2021. Through analysis of dissolved organic carbon (DOC) concentrations and optical properties, this study aimed to elucidate the spatial distribution patterns and biogeochemical transformations of DOM during estuarine mixing processes in the late flooding season of the Changjiang. DOC in our study ranged from 0.72 to 2.24 mg/L, with a mean (± standard deviation) of 1.15 ± 0.32 mg/L. The correlation with salinity clearly indicated the dual control of hydrodynamic mixing processes and localized organic matter inputs on DOM abundance. Spectroscopic characterization combined with PARAFAC modeling revealed the predominantly terrestrial signature of chromophoric DOM (CDOM) and its progressive transformation along the estuarine gradient. Notably, rapid consumption of protein-like fluorescent DOM (FDOM) was observed within the Changjiang Estuary’s low-salinity transition zone. The consistent decrease in DOM aromaticity (SUVA 254 decline of 0.13 L·mg C -1 ·m -1 per salinity unit, r 2 = 0.77) coupled with increasing spectral slope S 275-295 (an increase of 0.0006 nm -1 per salinity unit) clearly demonstrates selective removal of terrestrial constituents, and molecular weight reduction through estuarine processing. These results demonstrate that photochemical degradation might dominate CDOM removal in the Changjiang Estuary.

Winter Dormant Wheat Will Benefit From Mean Temperature Increase of 2°C When Well‐Watered and Fertilized in the Main Producing Regions of China - Ruoshi Wang; Chuang Zhao; Senthold Asseng; Bing Liu; Alex C. Ruane; Jiahui Cong; Xi Wang; Zhijuan Liu; Jin Zhao; Xiaoguang Yang (Global Change Biology, 2025)
Rising temperatures are projected to lead to a decline in global wheat production. However, this global trend belies the regional nuances of this impact, such as observed local yield increases in some field experiments in the winter wheat‐growing region of China. This study combines detailed data from eight field warming experiments and outputs of simulation by an ensemble of three point‐based crop models and an ensemble of 10 global gridded crop models to scrutinize the influence of warming on winter wheat yield in the main producing regions of China (MPC). Observed data were obtained from published reports of field experiments, where winter wheat was grown with sufficient water and nitrogen under free‐air‐temperature increase (FATI) by 2°C. Growth and physiology of winter wheat in the field experiments were simulated by three point‐based crop models to validate the effects of warming on wheat growth and yield as simulated by grid‐based crop models. Results of field observations and grid simulations both indicate notable increases in average grain yield (observed +13%, simulated +8%) and aboveground biomass (observed +15%, simulated +7%) under 2°C warming across the MPC. The winter dormancy and pre‐anthesis duration were shorter with warmer temperature, with the effect that the grain filling period between anthesis to maturity was extended by 6 days. The shorter phenology affected wheat photosynthesis because less solar radiation was available (−6%) over the growth period. However, the leaf area index started to develop earlier and reached a higher maximum than un‐warmed control, so the cumulative solar radiation for photosynthesis intercepted by warmed wheat was higher (+9%), as well as the radiation use efficiency (+1%). These findings suggest that well‐irrigated and well‐fertilized winter dormant wheat is likely to experience yield gains with local warming of up to 2°C, bolstering confidence in future adaptation of wheat production in China.

Unsupervised transfer learning for fault diagnosis across similar chemical processes - Ruoshi Qin; Feiya Lv; Huawei Ye; Jinsong Zhao (Process Safety and Environmental Protection, 2024)

Low-damage fetching method for pepper seedlings based on Res-Unet - Xin Jin; Shuang Chen; Lijun Zhao; Ruoshi Li; Qing Li; Song Gu; Guowei Liu; Jiangtao Ji (Computers and Electronics in Agriculture, 2024)

Characteristics of chromophoric dissolved organic matter in the Northern Andaman Sea - Ruoshi Zhao; Zhongqiao Li; Aung Aung Aye; Hao Zheng; Weifang Jin; Jingjing Zhang; Feng Zhou; Hongliang Li; Nang Mya Han; Myat Lwin; Jianfang Chen (Frontiers in Marine Science, 2023)
The dissolved organic matter (DOM) in the ocean is a large carbon pool that plays an important role in the global carbon cycle. Investigation of the characteristics and behaviors of DOM in some areas facilitates a better understanding of biochemical processes in the water column. In February 2020, water samples were collected to characterize the distribution and optical properties of DOM from the Northern Andaman Sea and the Northeastern Bay of Bengal. A high dissolved organic carbon (DOC) concentration appeared in the Northern Andaman Sea, which is strongly affected by the DOM contents of the Irrawaddy and Salween Rivers. A barrier layer that resulted from the freshwater input was observed above the thermocline. This layer was believed to have had a consistent effect on the concentration of DOM in the surface water and contributed to the differences in DOC concentration on each side of the Preparis Channel. Based on the fluorescence excitation emission matrix and parallel factor analysis, four fluorescent components were identified, including three humic-like components (C1, C2, and C4 with their maximal Ex/Em at ≤240/418 nm, 315/384 nm, and 270 (360)/442 nm and represented as peaks A, M, and A+C, respectively) and one protein-like component (C3 with maximal Ex/Em at 275/334 nm and represented as peak T). The humic-like components were mainly derived from terrestrial inputs. Low levels of humic-like components were confined in the upper water, with strong photodegradation in the euphotic zone. C3 was a typical tryptophan-like component that represented freshly produced autochthonous DOM. The correlation between C3 and biological index and apparent oxygen utilization suggested that it was highly bioavailable and not easy to be preserved in the deep sea. Overall, our results showed the distributions of DOM in the Northern Andaman Sea and the Northeastern Bay of Bengal and revealed the behaviors and controlling factors for DOM in the upper water.

Association of Sandstone-Type Uranium Mineralization in the Northern China with Tectonic Movements and Hydrocarbons - Yin Chen; Peisen Miao; Jianguo Li; Ruoshi Jin; Hualei Zhao; Lulu Chen; Cong Wang; Haoyu Yu; Xiaoru Zhang (Journal of Earth Science, 2022)

Covalently mucoadhesive amphiphilic prodrug of 5-fluorouracil for enhanced permeation and improved oral absorption - Yan Liu; Dongyang Zhao; Mengchi Sun; Wei Wei; Yingli Wang; Jiahua Zhou; Ruoshi Zhang; Jian Wang; Haotian Zhang; Zhonggui He; Qiming Kan; Jin Sun (Drug Delivery and Translational Research, 2018)